2018
DOI: 10.1109/tns.2018.2820658
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Loaded Scintillators Coupled to a Custom-Designed Silicon Photomultiplier Array for Neutron and Gamma-Ray Detection

Abstract: Scintillators capable of detecting both neutrons and gamma-rays have generated considerable interest. In particular, the use of such scintillators with silicon photomultipliers (SiPMs) enables low-power and compact-geometry applications. Three types of Li-loaded scintillators, CLYC, CLLB, and NaIL, have been tested with a custom-designed SiPM array for temperatures between -20 and 50 • C. The array consists of four 6x6 mm 2 SiPMs arranged in a 2x2 configuration. Pulse shape discrimination is used for neutron a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, the active constant temperature method inevitably increases the detector volume. There have been some studies to eliminate the temperature dependence by optimizing the bias voltage or pulse shape discrimination parameters [18,19]. However, most of the current studies used digitizers to store waveforms and optimize parameters through offline data processing, which is difficult to achieve miniaturization and ease of use.…”
Section: Jinst 17 T06005mentioning
confidence: 99%
“…However, the active constant temperature method inevitably increases the detector volume. There have been some studies to eliminate the temperature dependence by optimizing the bias voltage or pulse shape discrimination parameters [18,19]. However, most of the current studies used digitizers to store waveforms and optimize parameters through offline data processing, which is difficult to achieve miniaturization and ease of use.…”
Section: Jinst 17 T06005mentioning
confidence: 99%
“…Qiao et al [6] used the convolution neural networks to discriminate double Liang et al discus the effect of the temperature variation on the PSD result for a designed array of Silicon Photo-Multiplier (SiPM) coupled to Lithium-loaded scintillators. Results indicated that a poorer discrimination is obtained at high temperatures because of the thermal noise in SiPMs [7]. Yang et al investigated and compared four FPGA-based digital PSD methods.…”
Section: I In Nt Tr Ro Od Du Uc Ct Ti Io On Nmentioning
confidence: 99%